How to make the European Neighbourhood Policy more effective – new proposals of review of the European Union’s neighbourhood policy - Kalicka-Mikołajczyk, Adriana (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
The European Neighbourhood Policy (ENP) was developed in 2004, with the objective of avoiding the emergence of new dividing lines between the enlarged European Union (EU) and its neighbours and strengthening the prosperity, stability and security of all. It is based on the values of democracy, rule of law and respect of human rights. The ENP includes political association and deeper economic integration, increased mobility and more people-to-people contacts. The main objective of this paper is to asses all propositions, which has been made to offer more effective neighbouring policy and answer the question how the ENP should be reviewed in order to strengthen its visibility and effectiveness in building partnerships between the EU and the neighbouring partner countries. The events of recent years in the neighbouring partner countries have demonstrated the need for a new approach, a re-prioritization and an introduction of new ways of working the ENP. So, the main objective of the current review was to propose how the EU and its neighbours can build more effective partnerships in the neighbourhood. Differentiation and greater mutual ownership should be the hallmark of the new ENP, recognising that not all neighbouring countries aspire to EU rules and standards, and reflecting the wishes of each country concerning the nature and focus of its partnership with the EU. The public consultation has also demonstrated that while the offer of a closer relationship with the EU for those countries which have undertaken governance reforms has encouraged change in some countries, current practice and policy has been regarded by other partner countries as too prescriptive, and as not sufficiently reflecting their respective aspirations. The consultation has further indicated that ownership by both partners and the Member States needs to be stepped up; that cooperation should be given a tighter, more relevant focus; and that greater flexibility must be sought to enable the EU and its partners to respond to ever changing needs and circumstances. Within the ENP, the EU and the neighbouring partner countries should build stronger neighbourhood and stronger partnerships, be more focused on fewer priorities, which should reflect interests of both parties and where there should be greater involvement of the Member States.
Keywords: European Union; Article 8 TEU; revision; differentiation; European Neighbourhood Policy